Cognitive control moderates early childhood temperament in predicting social behavior in seven year old children: An ERP study - Lamm, Connie (Dev Sci, 2014)
Behavioral inhibition (BI) is a temperament associated with heightened vigilance and fear of novelty in early childhood, and social reticence and increased risk for anxiety problems later in development. However, not all behaviorally inhibited children develop signs of anxiety. One mechanism that might contribute to the variability in developmental trajectories is the recruitment of cognitive-control resources. The current study measured N2 activation, an ERP (event-related potential) associated with cognitive control, and modeled source-space activation (LORETA; Low Resolution Brain Electromagnetic Tomography) at seven years of age while children performed a go/no-go task. Activation was estimated for the entire cortex and then exported for four regions of interest: ventromedial prefrontal cortex (VMPFC), ventrolateral prefrontal cortex (VLPFC), dorsal anterior cingulate cortex (dorsal ACC), and dorsal lateral prefrontal cortex (DLPFC). BI was measured in early childhood (ages two and three years). Anxiety problems and social reticence were measured at seven years of age to ascertain stability of temperamental style. Results revealed that BI was associated with increased performance accuracy, longer reaction times, greater (more negative) N2 activation, and higher estimated dorsal ACC and DLPFC activation. Furthermore, early BI was only associated with social reticence at age 7 at higher (more negative) levels of N2 activation or higher estimated dorsal ACC or DLPFC activation. Results are discussed in the context of overcontrolled behavior contributing to social reticence and signs of anxiety in middle childhood.